Turning the Clock Ahead: Potential Preclinical and Clinical Neuropharmacological Targets for Alcohol Dependence - Leggio, Lorenzo; Cardone, Silvia; Ferrulli, Anna; A. Kenna, George; Diana, Marco; M. Swift, Robert; Addolorato, Giovanni (Current Pharmaceutical Design, 2010)
Treating alcohol use disorders represents a main goal in public health, but the effect of current medications is modest. Thus, in the last few years, research has been focusing on identifying new neuropharmacological targets for alcohol dependence. This review will summarize recent research, which has identified new targets to treat alcohol dependence. A variety of systems have been investigated, such as the endocannabinoid system, modulators of glutamatergic transmission, corticotropin-releasing factor (CRF), neuropeptide Y (NPY), nociceptin, glial cell line-derived neurotrophic factor (GDNF), acetaldehyde (ACD), substance P and Neurokinin 1 (NK1) receptor, nicotinic acetylcholine receptors (nAchRs), alpha-adrenergic receptor, and many others. Compared to preclinical studies, only a few clinical studies have been conducted so far. Thus, there is a critical need to translate successful preclinical results into human clinical trials. However, since some clinical studies have failed to replicate preclinical findings, future research will have not only to identify more efficacious medications, but also delineate the best match between a particular pharmacotherapy with a specific alcoholic subtype.
Keywords: pharmacotherapy